Mathematical modeling of evolutionary changes of oligonucleotide frequency patterns of bacterial genomes for genome-scale phylogenetic inferences - Reva, Oleg N. (University of Pretoria, 2019)
Thesis (PhD)--University of Pretoria, 2018.